Molecular profiling, including TERT promoter mutations, of acral lentiginous melanomas - Vazquez, Vinícius Lima (2016)
Acral lentiginous melanoma (ALM) is the less common subtype with singular characterization. TERT (human telomerase reverse transcriptase) promoter mutations have being described as recurrent in melanomas and infrequent in ALM, but their real incidence and clinical relevance is unclear. The objectives of this study were to describe the prevalence of TERT promoter mutations in ALM, and correlate with the molecular profile of other drive genes and clinical features. Sixty-one samples from 48 patients with ALM were analyzed. After DNA isolation, the mutation profiles of the hotspot region of BRAF, NRAS, KIT, PDGFRA, and TERT genes were determined by PCR amplification followed by direct Sanger sequencing. KIT, PDGFRA, and VEGFR2 gene amplification was performed by quantitative PCR. Clinical information such as survival, clinical stage, and Breslow tumor classification were obtained from medical records. TERT promoter mutations were found in 9.3% of the cases, BRAF in 10.3%, NRAS in 7.5%, KIT in 20.7%, and PDGFRA in 14.8% of ALM. None of the cases showed KIT, PDGFRA, or VEGFR2 gene amplification. We found an association between KIT mutations and advanced Clark level (IV and V, P=0.043) and TERT promoter mutations with low mitotic index. No other significant associations were observed between mutation profile and patients' clinical features nor survival rates. Oncogenic TERT promoter mutations are present in a fraction of ALMs. No relevant associations were found between TERT mutation status and clinical/molecular features nor survival. Mutations of KIT and PDGFRA are the most common genetic alterations, and they can be therapeutic targets for these patients.